2021
DOI: 10.1021/acsaem.1c02158
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite-Free and Micron-Columnar Li Metal Deposited from LiNO3-Based Electrolytes

Abstract: Rechargeable Li-metal anodes have received abundant attention for high-energy-density batteries. A solid electrolyte interphase (SEI) plays a significant role in regulating the Li + deposition/stripping process. Aimed to solve detrimental Li deposition with a dendritic and mossy morphology, herein, dendrite-free columnar Li deposition in micron size is constructed via creatively adopting a LiNO 3 -based electrolyte even at a high current density (2 mA cm −2 ) and areal capacity (4 mAh cm −2 ). N-rich inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…After getting decomposed the N adsorbs at the surface interacting with Li and Al forming compounds like Li x Al y N (Figure 3a). The favourable decomposition of NO 3 over PF 6 could be the reason that in experimental reports Li 3 N is found to be a major component of the formed SEI layer [16,25,48] . The quicker diffusion of NO 3 towards the surface compared to that of PF 6 during the simulation could be another reason (Figure S2a).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…After getting decomposed the N adsorbs at the surface interacting with Li and Al forming compounds like Li x Al y N (Figure 3a). The favourable decomposition of NO 3 over PF 6 could be the reason that in experimental reports Li 3 N is found to be a major component of the formed SEI layer [16,25,48] . The quicker diffusion of NO 3 towards the surface compared to that of PF 6 during the simulation could be another reason (Figure S2a).…”
Section: Resultsmentioning
confidence: 71%
“…[24] There are also reports of using LiNO 3 as additive in ether-based solvents, but they exhibit a lower electrochemical window. [16,25] On the other hand, this report showed that LiNO 3 with carbonate-based solvent can control uniform SEI deposition in a battery operating at higher voltage. [24] Lithium bis(fluorosulfonyl)imide (LiFSI) has also been used due to its ability to form a uniformly deposited SEI layer.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A columnar Li deposition is thus desirable. [133,134] Suitable external pressure is also favorable to maintain close contact between the individual Li particles and drive the lean electrolyte to effectively wet the newly formed Li surfaces. [43] Li metal anode matching high voltage cathode is desirable to render a high-energy-density pouch cell.…”
Section: Regulating Electrolytesmentioning
confidence: 99%